Optimalisasi Kelompok Sadar Wisata (Pokdarwis) Menuju Desa Wisata Di Desa Karanggupito Kecamatan Kendal Kabupaten Ngawi - Murti, Endang; Wiyaka, Agus; Iswati, Retno (JURNAL DAYA-MAS, 2020)
Abstract— Optimizing Tourism Awareness Groups (Pokdarwis) Towards Tourism Village in Karanggupito Village, Kendal District, Ngawi Regency. not to be aware of tourism in its natural potential, do not know the mapping of the area and business of guava and durian products, do not have a way of developing the quality of guava and durian fruit, and the diversification of healthy, hygienic and quality processed products in the context of economic empowerment of villagers. Limitations faced by the community build awareness and mindset of the community on natural tourism owned by the village and the large variety of plants, especially guava and durian trees which are one of the local wisdom possessed by the Karanggupito. Village community. Yodha Tama Youth Organization through integrated approaches, involving various scientific disciplines, every stage of the activity plan always involves citizens as partners and program implementers in an effort to encourage the progress of the village through the superiority of guava and durian as tourist icon icons with the aim of developing a group of people independently both economically and socially in terms of mapping the development and change area of Bukit Argo Munung tourism to become a tourist destination icon in Ngawi Regency. Keywords—: tourism awareness group (pokdarwis); tourism village; bukit tourism argo munung.